The responses of nursing system to the outbreak of SARS in a general hospital - 冯志英 杨晓秋 刘钰 袁彬 张黎明 王建荣 (Chinese medical journal, 2003)
Severe Acute Respiratory Syndrome (SARS), referred to as "contagious atypical pneumonia" is the fastest spreading communicable disease known in recent history. This disease is different from other kinds of respiratory contagion due to the following aspects, the syndrome happens quickly and the infectivity is high. New problems encountered by the nursing management staff are the precipitate,pestiferous, and large numbers of in-patients and the understanding of appropriate responses, within large complex hospitals, to ensure patient care is actively supported and infectivity is prevented. To deal with these problems, we implemented the following strategies, reinforcement of the management system; optimization of the nursing flow; amendments to related hospital policies; collection of relevant information; adherence to stringent disinfection protocols; isolation of areas; reallocation of hospital resources and more efficient utilization of resources. The above strategies have reinforced the nursing management system' s active response, guaranteed daily operation of the hospital' s nursing activities, including the quality of care provided by the nurses, and ensured the health of patients,nurses and doctors.